Karakteristik CEO dan Manajemen Laba - Dennis, Made Dwi Ariesta; Suhendah, Rousilita (Penerbit Goodwood, 2024)
Purpose: The aim of this study is to investigate the effect of Chief Executive Officer (CEO) characteristic, containing CEO age, CEO tenure, and CEO gender on the earnings management examined by the discretionary accruals among 42 firms listed on Indonesia Stock Exchange (IDX) for five years in 2018 until 2022. Results/findings: The results show that CEO age has no association with earnings management. CEO tenure has a significant positive association with earnings management, whereas CEO gender has a significant negative association with earnings management. Thus, to minimize earnings management, it is crucial to consider the length of time the CEO has been in their position (tenure). Contribution: The results of this study support both investors and creditors in determining which energy company credit offers to accept. Before making decisions about investments and credit, creditors and investors may take the CEO's traits into account. The CEO's traits may have an impact on the company's earnings management. Managers who are motivated by personal interests control earnings in the financial accounts. Good financial statements serve as the foundation for decisions made by creditors and investors. When earnings management is included, financial statements become unqualified and may cause consumers to be misled when making judgments.